Pemaknaan Klausula Menghadap Dalam Pelaksanaan Verlidjen Akta Notaril Melalui Media TeleKonfrensi di Era Digitalisasi - Abelia Lovena Sae; Dewati Candraningtyastuti (Jurnal Ilmu Kenotariatan)
Today's life cannot be separated from the development of science and technology such as the duties and roles of Notaries that require renewal to keep up with the times. Until now, the UUJN which has been in effect for approximately 10 years has not changed its contents. One thing that has not been regulated until now in the UUJN is regarding cyber notary. Therefore, the purpose of this writing is to analyze the interpretation of the "facing" clause on reading and signing of deeds using teleconference media in the digitalization era and to analyze the legal force of reading and signing of deeds using teleconference media reviewed based on the principles of cyber notary using normative legal research. Although the opportunity for verlijden and signing of deeds electronically in the ITE Law has been opened, this still cannot be done because there has been no change and opening of opportunities for verlijden and signing of deeds electronically in the UUJN. Reading and signing deeds with teleconference media can only be done with media registered with Kominfo namely through the Google Meets and Microsoft Teams applications or websites so that the deed is not degraded into a private deed. Special training is needed so that the obligations of a Notary continue to be run by current developments and updates to laws and regulations are required.